A CLINICAL STUDY ON KSHARAKARMA IN THE MANAGEMENT OF NASAPRATINAHA WITH SPECIAL REFERENCE TO HYPERTROPHIED INFERIOR TURBINATES - Sarmah, *Jyotirmoy; Mahanta, Hareswar; Rekha Sarma, Dipti (International Journal of Ayurveda and Pharma Research, 2017)
Nasal obstruction or stuffy nose, is one of the commonest presenting complaints in otorhinolaryngology clinics. If defects of the nasal septum are excluded, most commonly the problem can be attributed to the dysfunction of the nasal turbinates, mostly the inferior turbinates. Although every person experiences some degree of turbinate dysfunction at some point in life, persistent dysfunction is also not uncommon, involving approximately 50% of the population. In the short-term, the cases respond well to medical line of management which mainly constitute the use of decongestants, but their prolong use is not indicated because of health reasons. Similarly, the other medicines used, have only short-term benefits; once the inferior turbinates undergo submucosal fibrosis, then they become incapable of decongestion with medical line of management and those chronic cases of nasal obstruction need to be managed by surgical therapies only. Over the years, many surgical procedures have been employed for turbinate reduction, but incidences of complications, recurrence etc. along with the cost-factor mean that still there is much to be achieved in the management of hypertrophied turbinates of nose. Ksharakarma is a popular procedure of chemical cautery in Ayurveda, which has been used for centuries as a minimal invasive procedure for reduction of enlarged tissues. This study has been conducted to manage nasal obstruction, termed as Nasapratinaha in Ayurveda, due to hypertrophied turbinates, by application of Ksharakarma with significant results.